Home away from Home: Geography of Information and Local Investors - Bernile, Gennaro; Kumar, Alok; Sulaeman, Johan (Review of Financial Studies, 2015)
We develop a 10-K-based multidimensional measure of firm locations. Using this measure, we show that firm-level information is geographically distributed and institutional investors are able to exploit the resulting information asymmetry. Specifically, institutional investors overweigh firms whose 10-K frequently mentions the investors' state even when those firms are not headquartered locally and earn superior returns on those stocks. These ownership and performance patterns are stronger among hard-to-value firms. Local investor performance increases with the degree of local bias and with the local economic exposure of portfolio firms. Overall, geographical variation in firm-level information generates economically significant location-based information asymmetry.